2012
DOI: 10.1007/s13277-012-0360-0
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of galectin-1 during tumorigenesis of Opisthorchis viverrini infection-induced cholangiocarcinoma and its correlation with clinicopathology

Abstract: Galectin-1 is a beta-galactoside-binding lectin to function in cell adhesion, proliferation, differentiation, and might be involved in tumor progression and metastasis. In the present study, the expression kinetics of galectin-1 during the tumorigenesis of a parasite Opisthorchis viverrini infection-induced cholangiocarcinoma (CCA) was investigated in model animal hamsters, and the expression was confirmed in human CCA cases. It was found that galectin-1 was overexpressed at mRNA and protein levels with the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Our results could imply that the metastatic spread of malignant tumors involves a higher level of galectin-1 in the circulation. We are proposing that increasing the serum level of galectin-1 may favor metastasis by the following-mentioned modalities: (a) enhancing the adhesive interactions between tumor cells and the extracellular matrix proteins, such as laminin, fibronectin, and vitronectin [ 37 ]; (b) promoting tumor cell embolization through increased cell adhesion and dissemination of tumor cells in the circulation [ 38 , 39 ]; (c) elevating tumor vascular permeability [ 40 ]; and (d) conferring a selective survival advantage to metastatic cells (anoikis) [ 19 , 41 , 42 ]. Alternatively, galectin-1 serum levels may reflect an immune reaction to the tumor load from inflammatory cells that are known to express galectin-1.…”
Section: Discussionmentioning
confidence: 99%
“…Our results could imply that the metastatic spread of malignant tumors involves a higher level of galectin-1 in the circulation. We are proposing that increasing the serum level of galectin-1 may favor metastasis by the following-mentioned modalities: (a) enhancing the adhesive interactions between tumor cells and the extracellular matrix proteins, such as laminin, fibronectin, and vitronectin [ 37 ]; (b) promoting tumor cell embolization through increased cell adhesion and dissemination of tumor cells in the circulation [ 38 , 39 ]; (c) elevating tumor vascular permeability [ 40 ]; and (d) conferring a selective survival advantage to metastatic cells (anoikis) [ 19 , 41 , 42 ]. Alternatively, galectin-1 serum levels may reflect an immune reaction to the tumor load from inflammatory cells that are known to express galectin-1.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Gal-1 expression is regularly increased in tumor tissues since it can modulate cell adhesion, migration, survival and signaling [ 4 ]. At present, it has been clarified by some clinical studies that the expression of Gal-1 has close association with metastasis, recurrence and bad tumor prognosis, which includes cholangiocarcinoma [ 5 ], gastric cancer [ 6 8 ], gingival squamous cell carcinoma [ 9 ], hepatocellular cancer [ 10 12 ], renal cell cancer [ 13 ], head and neck squamous cell carcinomas [ 14 ], ovarian cancer [ 15 , 16 ], non-small cell lung cancer [ 17 , 18 ], classic Hodgkin lymphoma [ 19 ], laryngeal squamous cell carcinomas [ 20 ], glioblastoma [ 21 , 22 ] and so on. Nevertheless, we still don’t clearly know the impact of Gal-1 on the consistency and magnitude of the prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-cancer drug sunitibib malate inhibited the proliferation of CCA cell by suppressing PDGFRA signaling pathway, suggesting its potential as a target of therapy. Similarly, the increased expression galectin-1 was observed during tumorigenesis of O. viverrini infection-induced CCA, and in the tumor stroma of CCA cases [40]. High positive rate of immunostaining and correlation with stage, metastasis and cumulative overall survival indicated that galectin-1 is likely involved in the tumorigenesis, and expected to serve as a tumor stroma marker in diagnosis and prediction of metastasis and poor prognosis of the opisthorchiasis-associated CCA.…”
Section: Biomarkers Of Opisthorchiasis-associated Ccamentioning
confidence: 71%
“…progression of opisthorchiasis-associated CCA in animal model and human CCA. The location of the increased expression further suggested the involvement of galectin-1 in the CCA tumorigenesis, as the increased expression of the protein was mainly located in the epithelium of extensively proliferated and hyperplasia small bile ducts at early stage of CCA development, and in the extensive tumor stroma tissues at later stage, in both model animals and human CCA cases [40].…”
Section: Mechanism Of Tumorigenesis Of Opisthorchiasis-associated Ccamentioning
confidence: 86%